Analysis of Islamic Education Values in the Novel Kembara Rindu by Habiburrahman El Shirazy - Rizal, Syamsul (MODELING: Jurnal Program Studi PGMI, 2024)
This research aims to find out what Islamic education values are contained in the novel Kembara Rindu by Habiburrahman El Shirazy. This research is motivated by the existence of problems in the world of education such as social, cultural and so on, as educators or educated people must be able to find a way out to solve these problems. The way that can be done is through learning resources. One of the interesting learning resources can be done through reading materials, namely literary works. The bast seller novel whose story has many lessons and even Islamic education values that can be used as a learning resource is the novel kembara rindu by habiburrahman El Shirazy. This research is a type of library research (Library Reseach). The data collection technique used in this research is documentation, collecting various kinds of data in the form of writings that are relevant to the problems that are the focus of research. The data analysis technique used in this research is content analysis. The results showed that there are Islamic education values in the novel kembara rindu by Habiburrahman El Shirazy including the value of aqidah, such as faith in Allah, faith in the books of Allah, faith in the Messenger, faith in the last day and faith in 'qada and qadar. Furthermore, there is the value of worship, such as prayer, prayer and dhikr. And finally there are moral values, such as helping and gratitude.